Endothelial function and arterial stiffness in minimally symptomatic obstructive sleep apnea. - Kohler, M; Craig, S; Nicoll, D; Leeson, P; Davies, R; Stradling, JR (2008)
RATIONALE: Moderate-severe obstructive sleep apnea (OSA) is associated with endothelial dysfunction, increased arterial stiffness, and hypertension. It is not known whether minimally symptomatic OSA is also associated with impaired vascular function. OBJECTIVES: To determine whether minimally symptomatic OSA is associated with impaired vascular function. METHODS: In 64 patients (7 females) with minimally symptomatic OSA (oxygen desaturation index, 23.1 [SD, 15.6]; Epworth Sleepiness Scale score, 8 [SD, 3.8]), and 15 matched control subjects without OSA, endothelial function was assessed by ultrasonographic measurement of flow-mediated dilatation, and by applanation tonometry-derived pulse wave analysis (forearm ischemia and salbutamol-induced changes in augmentation index, AI(x)). Arterial stiffness was assessed by AI(x) and ambulatory blood pressure (ABP) was measured over 1 week. MEASUREMENTS AND MAIN RESULTS: In patients with OSA, flow-mediated dilatation was significantly lower than in control subjects (5.0% [SD, 2.7%] and 7.5% [SD, 3.3%], respectively; P = 0.003). AI(x) was significantly higher in the OSA group compared with the control group (26.0% [interquartile range (IQR), 19.0-29.5%] and 21.0% [IQR, 8.0-27.0%], respectively; P = 0.04). Change in AI(x) after both forearm ischemia and salbutamol was significantly smaller in patients with OSA (-2.0% [IQR, -5.0 to +4.0%] and -3.0% [IQR, -7.0 to 0.0%], respectively), than in control subjects (-6.0% [IQR, -8.0 to -5.0%] and -7.0% [IQR, -10.0 to -3.0%]; P = 0.005 and P = 0.04, respectively). ABP was similar (97.6 mm Hg [SD, 7.9 mm Hg] and 94.8 mm Hg [SD, 7.4 mm Hg], OSA and control groups, respectively; P = 0.21). CONCLUSIONS: In patients with minimally symptomatic OSA, diverse properties of endothelial function are impaired and arterial stiffness is increased. Although this was not associated with a significantly increased ABP, the findings suggest that patients with minimally symptomatic OSA are at increased cardiovascular risk.